The Impact of the Covid-19 Pandemic on the Hungarian Penitentiary System and Its Transformation Processes - Czenczer, Orsolya (Magyar Rendészet, 2023)
The Covid-19 epidemic has put significant pressure on national penitentiary services all over the world to control the impacts that the pandemic has on closed prison environments. The prison services of the member states of the Council of Europe have responded with incredible speed and effectiveness with preventive and administrative measures to prevent the spread of the virus. The objective of the Council of Europe, EuroPris and other international organisations, was to support the member states’ responses to the situation in prisons by facilitating the exchange of information and best practices. The present study examines the statements and recommendations of the most important bodies and committees of the Council of Europe, in parallel with measures and solutions implemented in Hungary, in the light of international recommendations. The paper is based on a descriptive analysis of the Council of Europe expectations and recommendations and their applicability in the Hungarian prison system. Hungary has successfully processed and incorporated mostly all of the expectation of the international parties, in fact, he took further steps to make the pandemic’s outreached contacts of prisoners and relatives more colourful and active. Prevention and control measures adopted in timely manner were effective also in Hungary, as well in other Council of Europe member state. This study highlights the critical importance of fast and reasonable actions of international control bodies and the open and cooperative response of the national prison services.